Analisis Geometri Atap Rumah Adat di Kampung Weeyelo Desa Kabukarudi Kecamatan Lamboya Kabupaten Sumba Barat: Rumah adat - Langu, Albertina; Ata, Elda Rambu; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
The objective of this research is to analyze the two-dimensional geometric shapes found in the roof structures of traditional houses in Weeyelo Village, Kabukarudi, Lamboya District, West Sumba Regency, as part of the fulfillment of course requirements in accordance with the title agreed upon with the supervising lecturer. This study was conducted through interviews with several traditional leaders and by means of documentation to obtain authentic data.The traditional Sumbanese house represents a cultural heritage that functions as both a dwelling place for the adherents of the Marapu belief system and as a sacred space (mbara) for worshiping God through the spirits of the ancestors. Thus, the traditional house also serves as a “church” or place of worship for the Marapu community. According to traditional leaders, the traditional house holds a central role in Sumbanese culture and must be preserved as a way to honor the legacy of the ancestors. The traditional hou eis regarded as the “house of God” that unites people in a spiritual space, where they perform rituals and prayers (mbara) in accordance with their faith and belief.From a mathematical perspective, the traditional Sumbanese house contains various geometric elements, such as two-dimensional and three-dimensional shapes, similarity, and congruence. In addition, the houses are decorated with carved ornaments, which are creative cultural expressions passed down through generations and preserved as part of local identity.